Designing a Multimodal Feedback Component for VR Applications - Magalhães, Gabriel; Fonseca, Davi; Amorim, Glauco; Viana, Windson; Santos, Joel dos (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the Web, 2025)
Virtual Reality (VR) environments have shown great potential across a wide range of applications that benefit from interaction through touch and haptic feedback, such as entertainment, education, and rehabilitation. By simulating realistic tactile sensations, such as contact, texture, and pressure, VR systems can enhance user engagement, accessibility, and understanding of virtual worlds. In this context, haptic-enabled VR applications can play a fundamental role in diverse scenarios that demand precise object manipulation and spatial awareness. This paper presents a multimodal feedback system for VR applications to provide precision in object recognition using headset controllers and their collision with virtual objects. The proposed system generates haptic feedback regarding three types of collision: touch, stroke, and entering. It is intended to increase the user experience and sense of presence. In the evaluation, most users reported being satisfied with the application and stated that it provided a good sense of presence. They also found that, among the vibration patterns, the irregular one was the most successful in conveying the intended texture.